WAS MARGINAL SCIENTIFIC REVOLUTION UNIQUE IN HISTORY OF ECONOMIC THOUGHT? - Antonov, Alexey (Revista Inclusiones, 2020)
The immediacy of the problem under study stems from the fact that there is a growing need for new comprehension principles of the changes that occur in the modern economy in the context of economic life globalization and slowdown in global economic growth. In this regard, the economic doctrines discarded by history deserve new reading. The purpose of this article is to return researchers’ attention to the problem of continuous/discontinuous development of economic thought. The key approach to dealing with this problem lies in the methodological principles of scientific knowledge development established by T. Kuhn and I. Lakatos and claiming that all sciences progress via revolutionary paradigm shifts. Contrary to this, history of economic doctrines generally includes only one scientific revolution – substitution of the labour theory of value for the marginal utility theory. This article proves that the forgoing misrepresents real development of economic thought. The reason for the current situation is failure to comply with the methodological principle of a uniform approach to examined phenomena. The marginal scientific revolution shifted focus of economic processes from production relations to consumption relations. However, there were no scientific revolutions in other cases of similar substitution of reproduction relations. The methodological intention of the article is to carry out a consistent analysis of social conditions of goods production in connection with to all new schools emerging in economic science rather than to make an exception for the marginalist economic school alone. Such approach allows discovering the forgotten scientific revolutions which actually happened once in the history of economic thought. This fills up the gap existing in economic theory. The content of the article can be used to correct education courses on the history of economic thought.